A review of the Sustainable Development Goals policy framework for Malaysian local governments / Khairin Nazry Karim - Karim, Khairin Nazry (Universiti Teknologi MARA, Perak, 2021)
Currently, there are wide-ranging policies available on sustainable development from the Government of Malaysia. There is a need for a literature to be used as the point of departure for sustainable development discussion. This paper aims to serve as a one-stop centre for easyreferencing on Sustainable Development Goals (SDGs) policies in Malaysia. The paper first presented the background on sustainable development and Malaysian governance structure to provide context. Further along, the paper summarises the policy framework on Sustainable Development Goals under the Ministry of Housing and Local Government's ambit with particular attention to local governments. Findings showed that the Malaysian government do not lack the effort and desire to achieve SDGs. Sustainable development concept has been embroidered into numerous policy and governance framework. Local governments should treat policies as a tool and means of SDGs implementation at their municipalities. As public policy undergoes constant changes and modification, having a sound foundation on public policy can lead to better judgement and decision making.